SAMAN DANCE OF THE ACEH PEOPLE: IDENTITY AND ACTUALIZATION - Heniwaty, Yusnizar (Universitas Negeri Medan, 2018)
AbstractThis study aims to analyze the Saman dance of the Aceh people that focuses on the analysis of the function of Saman that becomes the identity of the Gayo people. The identity and the actualization of Saman in accordance to the religion and customs of the Gayo people include some aspects that create the dance of the Aceh people, such as: socio-religious life, philosophies, symbols, norms and ethics. In the analysis, Saman has some values that make it as the identity of the Aceh people in the present and future life.Keywords: Saman Dance, Identity, Actualization